On the interaction between radon progeny and particles generated by electronic and traditional cigarettes. (April 2015) - Vargas Trassierra, C.; Cardellini, F.; Buonanno, G.; De Felice, P.
Abstract: During their entire lives, people are exposed to the pollutants present in indoor air. Recently, Electronic Nicotine Delivery Systems, mainly known as electronic cigarettes, have been widely commercialized: they deliver particles into the lungs of the users but a "second-hand smoke" has yet to be associated to this indoor source. On the other hand, the naturally-occurring radioactive gas, i.e. radon, represents a significant risk for lung cancer, and the cumulative action of these two agents could be worse than the agents separately would. In order to deepen the interaction between radon progeny and second-hand aerosol from different types of cigarettes, a designed experimental study was carried out by generating aerosol from e-cigarette vaping as well as from second-hand traditional smoke inside a walk-in radon chamber at the National Institute of Ionizing Radiation Metrology (INMRI) of Italy. In this chamber, the radon present in air comes naturally from the floor and ambient conditions are controlled. To characterize the sidestream smoke emitted by cigarettes, condensation particle counters and scanning mobility particle sizer were used. Radon concentration in the air was measured through an Alphaguard ionization chamber, whereas the measurement of radon decay product in the air was performed with the Tracelab BWLM Plus-2S Radon daughter Monitor. It was found an increase of the Potential Alpha-Energy Concentration (PAEC) due to the radon decay products attached to aerosol for higher particle number concentrations. This varied from 7.47 ± 0.34 MeV L −1 to 12.6 ± 0.26 MeV L −1 (69%) for the e-cigarette. In the case of traditional cigarette and at the same radon concentration, the increase was from 14.1 ± 0.43 MeV L −1 to 18.6 ± 0.19 MeV L −1 (31%). The equilibrium factor increases, varying from 23.4% ± 1.11% to 29.5% ± 0.26% and from 30.9% ± 1.0% to 38.1 ± 0.88 for the e-cigarette and traditional cigarette, respectively. These growths still continue for long time after the combustion, by increasing the exposure risk. Highlights: Co-exposure to radon progeny and second hand aerosol from e-cigarette was evaluated. The experimental campaign was carry out in ad-hoc chamber. Calibrated instrumentation was used for radon progeny and airborne particle measurement. Changes in Potential Alpha Energy Concentration and Equilibrium Factor were estimated. The results show an increasing exposure risk.